On the indecomposable involutive set-theoretic solutions of the Yang-Baxter equation of prime-power size. Issue 5 (3rd May 2020) - Castelli, M.; Pinto, G.; Rump, W.
Abstract: We develop a method to construct all the indecomposable involutive non-degenerate set-theoretic solutions of the Yang-Baxter equation with a prime-power number of elements and cyclic permutation group. Moreover, we give a complete classification of the indecomposable ones having abelian permutation group and cardinality pq (where p and q are prime numbers not necessarily distinct).